Knowledge, attitudes, practices (KAP), and risk factors toward zoonotic diseases among smallholder livestock farmers in Bugesera district of Rwanda - Munyaneza, Celestin; Bizimana, Ferdinand; Mukumbo, Felicitas; Gatesi, Sandrine; Sibomana, Ephrem; Munyampuhwe, Severin; Dutuze, Marie Fausta (Frontiers in Public Health, 2025)
BackgroundAlthough zoonotic diseases pose significant health and economic threats globally, rural communities in developing countries are more vulnerable due to the increased proximity between animals and humans and the lack of knowledge about these diseases. This study assessed the knowledge, attitudes, practices (KAP), and risk factors regarding zoonotic diseases among smallholder livestock farmers in Bugesera district of Rwanda.Methods and materialsA convenient sample of 155 livestock smallholder farmers was selected from eight of the fifteen sectors of the district. Data were collected through interviews using a semi-structured questionnaire. Descriptive analyses including frequencies and means were used to summarize the data. Pearson’s chi-square test was used to examine associations between knowledge and socio-demographic variables and between knowledge and practices.ResultsFindings showed that 50.3% of respondents knew diseases could be transmitted from animals to humans and just 13.5% recognized reverse zoonotic transmission - humans to animals. When specifically asked if they knew about brucellosis, tuberculosis, and Rift Valley fever; 88, 79, and 41% of respondents, respectively, reported being familiar with these diseases though many were unaware of their zoonotic nature. Risky attitudes and practices were prevalent, including the lack of isolation for sick animals (70.97%) and failure to quarantine newly introduced animals (83.87%). While 81.94% vaccinated their animals, only 16.54% could specify at least one vaccinated disease, and none knew the date of their animals’ next vaccination date. Other poor practices were reported, with 64.52% not separating animal and human utensils, and only 25.81% of cattle owners reported using artificial insemination. Additionally, 34.46% consumed raw non-boiled milk, and 24.5% did not use mosquito nets. Regarding roaming animals in the neighborhood, 79% of rats, 55% bats, 68% dogs, 67% cats, and 5.2% monkeys.ConclusionThe study revealed low awareness and high-risk practices regarding zoonotic diseases among smallholder livestock farmers in Bugesera district, posing a significant One Health concern. Therefore, educational programs to improve KAP and strengthen zoonotic disease prevention efforts in this district.